Komischer Diskurs: kognitiv und kulturbedingt - Oksana Zubach (Linguistische Treffen in Wrocław)
This article presents the research results that are dedicated to the peculiarities of the German laughter culture. The research is based on the foundations of pragmatics and is carried out using the integrative approach so that contextual, content, functional and structural features of the text are addressed. A significant subject in the broad field of discourse was and still is the area of the comic (humor, jokes, satire). The article accepts relevant criteria (sociological, psycholinguistic, communicative, pragmatic, gender-sensitive, etc.) that reflect the expression of humorous elements in the German language and culture. The analysis of comic discourse focuses on the interaction between the sender of information, who conveys his own intentions in the statement, and the recipient of information, who in turn interprets information in terms of background knowledge. Comic discourse is viewed in a broad social context. The cognitive correlate of a comic discourse is the basic system of knowledge about a situation and its planning, production and acceptance. The study focuses on comic texts from Internet sources that reflect people’s attitudes through comments not only on comic texts as a means of entertainment, but also on situations and phenomena. The comic texts are described as a hallmark of the German laughter culture. The comic effect in the text is based on communication expectations, on variations in reality, on juggling with objects, issues, facts, and the reflection of human adaptation in all areas of the target language culture.